Assessment methodology for human-exoskeleton interactions: Kinetic analysis based on muscle activation - Fanti, Vasco; Sanguineti, Vittorio; Caldwell, Darwin G.; Ortiz, Jesús; Di Natali, Christian (Frontiers in Neurorobotics, 2022)
During the development and assessment of an exoskeleton many different analyses need to be performed. The most frequently used evaluate the changes in muscle activations, metabolic consumption, kinematics and kinetics. Since human-exoskeleton interactions are based on the exchange of forces and torques, the latter of these, kinetic analyses, are essential and provide indispensable evaluation indices. Kinetic analyses, however, require access to, and use of, complex experimental apparatus, involving many instruments and implicating lengthy data analysis processes. The proposed methodology in this paper, which is based on data collected via EMG and motion capture systems significantly reduces this burden by calculating kinetic parameters, such as torque and power, without needing ground reaction force measurements. This considerably reduces the number of instruments used, allows the calculation of kinetic parameters even when the use of force sensors is problematic, does not need any dedicated software and will be shown to have high statistical validity. The method, in fact, combines data found in the literature with those collected in the laboratory, allowing the analysis to be carried out over a much greater number of cycles than would normally be collected with force plates, and thus enabling easy access to statistical analysis. This new approach evaluates the kinetic effects of the exoskeleton with respect to changes induced in the user's kinematics and muscular activations patterns, and provides indices that quantify the assistance in terms of torque (AMI) and power (API). Following the User-Centre Design approach, which requires driving the development process as feedback from the assessment process, this aspect is critical. Therefore, by enabling easy access to the assessment process, the development of exoskeletons could be positively affected.